2022
DOI: 10.3390/diagnostics12092163
|View full text |Cite
|
Sign up to set email alerts
|

Understanding COVID Vaccination and Its Implication in Cancer Patients’ Imaging of Lymph Nodes by PET-CT

Abstract: (1) Background: The appearance of enlarged lymph nodes on imaging adds another layer of complexity to the differential diagnosis of disease progression versus immune response to COVID-19 vaccines. Our aim was to find an optimal timing between the vaccination and the PET-CT scan. (2) Methods: 25 cancer patients with 18F-FDG PET-CT evaluations and a history of COVID-19 vaccination between September 2021 and December 2021 were retrospectively analyzed to characterize the lymph nodes related to the time interval f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
(34 reference statements)
0
1
0
Order By: Relevance
“…The antigens present in the vaccines interact with the host leading to increased immunological response, which leads to inflammatory reaction at the site of injection and surrounding lymphoid tissue. The inflammatory changes are due to release of proinflammatory cytokines such as tumor necrosis factor alpha (TNF-α), prostaglandins, and interleukins (IL-1 and 6), by immune cells such as macrophages, dendritic cells, and monocytes mimicking innate and adaptive immune response to a natural infection, resulting in lymphadenopathy with swollen and occasionally painful lymph nodes [18] , [19] , [20] , [21] .…”
Section: Discussionmentioning
confidence: 99%
“…The antigens present in the vaccines interact with the host leading to increased immunological response, which leads to inflammatory reaction at the site of injection and surrounding lymphoid tissue. The inflammatory changes are due to release of proinflammatory cytokines such as tumor necrosis factor alpha (TNF-α), prostaglandins, and interleukins (IL-1 and 6), by immune cells such as macrophages, dendritic cells, and monocytes mimicking innate and adaptive immune response to a natural infection, resulting in lymphadenopathy with swollen and occasionally painful lymph nodes [18] , [19] , [20] , [21] .…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, myocarditis associated with DRESS is associated with a similarly high mortality rate, approximately 40% [72]. When comparing the rarity of Immune Checkpoint Inhibitor-Induced Myocarditis to COVID-19-associated myocarditis, this discrepancy may stem from challenges related to misclassification and the intricate diagnosis of cardiac events triggered by ICIs, or other rare and unexpected adverse events related to the COVID-19 vaccine, particularly amid the ongoing COVID-19 pandemic [73][74][75][76][77][78]. A systematic review encompassing 43 articles, ultimately identified 51 patients with COVID-19-associated myocarditis based on clinical diagnosis.…”
Section: Managementmentioning
confidence: 99%